Initial herbivory and exposure to herbivory-induced volatiles enhance arthropod species richness by diversifying community assemblages - Yoneya, Kinuyo; Miki, Takeshi; Takabayashi, Junji (Frontiers in Ecology and Evolution, 2023)
Plant ecological traits affect the species identity of plant-colonizing arthropods, which in turn induces species-specific trait changes in plants, forming feedback between plants and arthropods. Such feedback can amplify initial differences in species composition, leading to large variations (i.e., high β diversity). We hypothesized that the differences in plant initial conditions have sustained effects on arthropod community composition and species richness. To test this hypothesis, we monitored arthropod community assembly on a willow tree species, Salix eriocarpa, which was experimentally manipulated into three initial treatments: undamaged (in chamber 1); damaged by the specialist leaf beetle, Plagiodera versicolora (chamber 2); and “exposed” plants that were undamaged but were exposed to volatiles from damaged plants (in chamber 2). The arrival and population dynamics of the leaf beetle were affected by the plant’s initial condition (chamber 1 vs 2), which could result from the microscale environmental heterogeneity between chambers (chamber effect) and/or from the herbivory-related impacts (direct herbivory and exposure to induced volatiles in chamber 2). The community composition on damaged and exposed plants became significantly different on day 32. In addition, the divergence in composition between plant individuals was significantly smaller in undamaged plants (chamber 1) than in damaged and exposed plants (chamber 2) on day 60. The compositional variations (β diversity) between chambers, between treatments, and between days, comprised a large proportion (two third) of the total species richness ( diversity) in the whole community of arthropods. These results suggest that plant initial condition is a key driver of community assembly and the maintenance of species diversity.